B-type natriuretic peptide reference interval of newborns from healthy and pre-eclamptic women: a prospective, multicentre, cross-sectional study. Issue 10 (17th October 2018) - Rodriguez, David; Garcia-Rivas, Gerardo; Laresgoiti-Servitje, Estibalitz; Yañez, Jesus; Torre-Amione, Guillermo; Jerjes-Sanchez, Carlos
Abstract : Objective: To define and compare the reference interval of B-type natriuretic peptide (BNP) in healthy newborns (HN) from healthy mothers and with severe pre-eclampsia. Design: Prospective, multicentre, cross-sectional study. Setting: Four obstetric wards of second-level academic hospitals. Participants: 167 HN, from 146 healthy and 21 severe pre-eclamptic women. We included newborns from healthy mothers with full-term pregnancies (38 to 42 gestational weeks), who received adequate prenatal care and who had Apgar scores ≥7 at 0 and 5 min. Newborns with chromosomopathies identified during prenatal consultations, those with respiratory distress and those with cardiac or pulmonary disease detected in the first paediatric evaluation were excluded from this study. In the group of pre-eclamptic women, we considered the same inclusion criteria, but the patients also had to meet the diagnostic criteria for pre-eclampsia with severity features, according to the American College of Obstetricians and Gynaecologists guidelines. The same exclusion criteria used for the healthy group were applied to the pre-eclampsia-associated newborn. Interventions: A single blood sample from the umbilical cord artery after delivery (vaginal or caesarean section). Primary outcome: Reference level of BNP in HN. Results: In the HN group, the median BNP was 12.15 pg/mL (IQR 7.7–16.8 pg/mL) and in the pre-eclamptic group 20.8 pg/mL (IQR 5.8–46.5 pg/mL). The reference interval for BNP in HN was 5pg/mL (95% CI 5 to 5) to 34 pg/mL (95% CI 28.4 to 38.8). We identified higher expression of BNP in newborns from pre-eclamptic women overall (p=0.037, r=0.16) and in newborns exposed to stress conditions, such as complications during labour and delivery (p=0.004, r=0.33). Conclusions: In HN, BNP concentrations at birth were lower than reported in other similar populations. In neonates with stress conditions, the higher expression of this biomarker establishes another possible link between stress and the cardiovascular response. Trial registration number: NCT02574806 ; Pre-results.